Length-Weight Relationship and Condition Factors of Sea Cucumber on Mare and Moti Islands Conservation Areas in North Maluku - Ramili, Yunita; Umasangaji, Halikuddin; Legohiwo, Misnawati (Jurnal Kelautan Tropis, 2024)
This work aimed at determining the growth patterns and condition factors of three sea cucumber species, namely Holothuria atra, Bohadschia marmomata, and B. vitiensis in seagrass beds of Mare and Moti Islands. Samples were collected in March 2023 using a roaming survey method in a block area with an area of 5000 m2.  As amount of 54 sea cucumbers were analysed from Mare Island and 58 individuals from Moti Island. The results of this study indicate that the correlation (r) length-weight relationship for the three sea cucumber species is stronger (r > 0.6) on Moti Island than Mare Island.  H. atra and B. marmorata have a negative allometric growth pattern, while B. vitiensis has a positive allometric growth pattern on both islands. The Fulton condition factors for the sea cucumbers assessed on Mare Island were recorded for H. atra of 2.84 ± 2.01, B. marmorata of 3.13 ± 2.47 and B. vitiensis of 9.24 ± 5.73. Meanwhile, at Moti Island were found for H. atra of 12.49 ± 11.66, B. marmorata of 9.58 ± 7.38, and B. vitiensis of 8.87 ± 3.68. This is indicated that all sea cucumber species are in good physical condition. Meanwhile, the relative weight condition factor (Wr) of the three species of sea cucumbers on both islands were in the range above 100, which indicated a food surplus in their habitat. The results of this research can be important as the preliminary data in terms of sustainable management of sea cucumber stocks in North Maluku.